Managing agricultural water resources: Addressing the complexity of innovation, social perspectives, and water governance in Sri Lanka. (24th February 2022) - Jayasiri, Maveekumbure Manthreethilaka Jayasiri Gamaralalage Chathuri Nishanka; Yadav, Sudhir; Dayawansa, Nandani Dhammika Kumari; Ingold, Karin
Abstract: Irrigation plays a vital role in world food security. Agriculture accounts for 70% of freshwater withdrawals worldwide, and the figure is even higher in developing countries like Sri Lanka. The rapid expansion of anthropogenic activities, together with the anticipated climatic risks associated with them, is exacerbating the problem of increasing agricultural water demand. Although it has been recognized for decades, improving irrigation water‐use efficiency and water productivity is still considered the most realistic option for addressing the challenge of sustainable management of water resources. However, adoption of recommended water‐efficient technologies and concepts remains elusive in practice, highlighting the gaps created by failing to consider social perspectives in developing water management strategies. As a result, the effectiveness of water governance has often been questioned in terms of performance and adoption of innovative technologies. This paper reviews and discusses the complexity of innovation through a technical, social, and institutional lens by reviewing available research on Sri Lanka's river basins and presents a perspective on opportunities for improving irrigation water management. Abstract: L'irrigation joue un rôle vital dans la sécurité alimentaire mondiale. L'agriculture représente 70% des prélèvements d'eau douce dans le monde, et ce chiffre est encore plus élevé dans les pays en développement comme le Sri Lanka. L'expansion rapide des activités anthropiques, ainsi que les risques climatiques anticipés qui y sont associés, exacerbent le problème de l'augmentation de la demande en eau agricole. Bien qu'elle soit reconnue depuis des décennies, l'amélioration de l'efficacité de l'utilisation de l'eau d'irrigation et de la productivité de l'eau est toujours considérée comme l'option la plus réaliste pour relever le défi de la gestion durable des ressources en eau. Cependant, l'adoption de technologies et de concepts économes en eau recommandés reste insaisissable dans la pratique, ce qui met en évidence les lacunes créées par l'absence de prise en compte des perspectives sociales dans l'élaboration de stratégies de gestion de l'eau. En conséquence, l'efficacité de la gouvernance de l'eau a souvent été remise en question en termes de performance et d'adoption de technologies innovantes. Cet article passe en revue et discute la complexité de l'innovation à travers une optique technique, sociale et institutionnelle en passant en revue les recherches disponibles sur les bassins fluviaux du Sri Lanka et présente une perspective sur les opportunités d'amélioration de la gestion de l'eau d'irrigation.